2008
DOI: 10.1111/j.1574-695x.2008.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PER-1 extended-spectrum β-lactamase producingPseudomonas aeruginosaclinical isolates of the international clonal complex CC11 from Hungary and Serbia

Abstract: PER-1 extended-spectrum beta-lactamase-producing Pseudomonas aeruginosa clinical isolates from Budapest, Hungary, and Belgrade, Serbia, were characterized by molecular methods. Two PER-1-positive isolates were recovered from sporadic cases in Budapest and a small cluster of PER-1-positive infections involving four patients were identified at a Belgrade hospital. A class 1 integron harbouring a bla(OXA-2)beta-lactamase gene and four other gene cassettes was detected in both the Budapest and the Belgrade isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…ST235 was the founder ST of the clonal complex CC235 (previously described as CC11/BG11). CC235 has been long known as responsible for outbreaks throughout Europe, Asia, and South America (8,11,15,17,18,20,27) while armed with various ESBLs (such as PER-1, GES-1, and BEL-1) as well as MBLs (such as VIM-1, VIM-4, and IMP-1) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…ST235 was the founder ST of the clonal complex CC235 (previously described as CC11/BG11). CC235 has been long known as responsible for outbreaks throughout Europe, Asia, and South America (8,11,15,17,18,20,27) while armed with various ESBLs (such as PER-1, GES-1, and BEL-1) as well as MBLs (such as VIM-1, VIM-4, and IMP-1) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of P. aeruginosa to accumulate overproduction of intrinsic resistance mechanisms, as well as the combination of various genetic determinants, including nonplasmid lateral exchange of resistance regions (21), results in multidrug-resistant or extensively drug-resistant isolates. Multilocus sequence typing, conducted according to published protocols (28; http://pubmlst.org/paeruginosa/), assigned HIABP11 to sequence type 235 (ST235), which has been encountered in clinical and environmental isolates of different countries (29,30), including Serbia (31). ST235 is the primary founder of the successful epidemic clonal complex 235 (CC235), associated with various ␤-lactamase genes, including PER-1 extended-spectrum ␤-lactamase and VIM-type metallo-␤-lactamases (32,33).…”
mentioning
confidence: 99%
“…The rate of bla PER-1 -positive isolates estimated at our hospital is mostly due to clonally related strains, and it is lower than the rates observed at other hospitals in our country (1,13,14). Studies conducted in other countries have reported lower rates of bla PER-1 -positive isolates compared to Turkey; however, these studies also showed that these percentages tend to increase when specific selection criteria are applied (15,16). In the present study, our results showed a nearly homogenous distribution of the bla PER-1 -positive P. aeruginosa isolates across the hospital wards; on the other hand, most of the bla PER-1 -positive A. baumannii complex bacteria were isolated from the emergency intensive care unit.…”
mentioning
confidence: 73%